Optimizing accounting decision making using goal programming - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2019)
Goal programming is a decision‐making technique that seeks to help decision makers make decisions that satisfy competing goals to the best extent possible. This article provides a description of goal programming, demonstrates how it can be implemented on a spreadsheet, and illustrates its use through an example from management accounting.